KONSEKUENSI PERBEDAAN FIKIH TERHADAP KAIDAH FIKIH - Parman Komarudin; Muhammad Rifki Hidayat (STAI AL FALAH Banjarbaru, 2019)
Fiqih is the result of ulama’s ijtihad, could be changed and has a different opinion in some problems which is the forerunner of mazhab fiqih’s upcoming. Kaidah Fiqih is one of platform that is no less important compared with other supporting dalil for mujtahid in making easy to know Islamic law. This article tries to explain and explore the qonsequences against differences in kaidah fiqih. This article included in the literature search by using a normative juridical method. The result shows that differences of mazhab fiqih at least produces two qonsequencies. The first, there is mazhabfiqih that only adopted by one mazhab. The second, there is certain kaidah fiqih that understood differently by each mazhabs. Keywords: Consequency, Fiqih, Kaidah fiqih